Calculation of thermodynamic parameters of metals - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
Method of calculation of thermodynamic parameters of metals has been developed. Based on the thermodynamic parameters of the metals, it is shown that the Gibbs molar volumetric energy has a negative value. When metals are heated, Gibbs molar volumetric energy decreases. The heating and cooling processes are reversible. Metal crystallization occurs under thermodynamically equilibrium conditions.